2005
DOI: 10.1104/pp.104.057745
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Insensitivity Conferred by theGreen-ripeandNever-ripe 2Ripening Mutants of Tomato

Abstract: The ripening of a fleshy fruit represents the summation of an array of biochemical processes that are regulated by interactions between developmental programs and environmental inputs. Analysis of tomato (Solanum lycopersicum) mutants and inhibitor studies indicate that ethylene is necessary for full development of the ripening program of climacteric fruit such as tomato, yet ethylene alone is not sufficient. This suggests that an interaction between ethylene and nonethylene (or developmental) pathways mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
93
0
3

Year Published

2011
2011
2012
2012

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 114 publications
(101 citation statements)
references
References 45 publications
5
93
0
3
Order By: Relevance
“…The Gr mutant and CaMV35S::SlGR overexpression lines display a reduced response to ethylene-induced floral abscission that lies between that observed in control and Nr plants (Barry et al, 2005;Barry and Giovannoni, 2006). Similarly, the CaMV35S::SlGRL1 lines have reduced rates of ethylene-induced floral abscission, comparable to those of the Gr mutant (Fig.…”
Section: Responsiveness (Fig 4e; Supplementalmentioning
confidence: 62%
See 4 more Smart Citations
“…The Gr mutant and CaMV35S::SlGR overexpression lines display a reduced response to ethylene-induced floral abscission that lies between that observed in control and Nr plants (Barry et al, 2005;Barry and Giovannoni, 2006). Similarly, the CaMV35S::SlGRL1 lines have reduced rates of ethylene-induced floral abscission, comparable to those of the Gr mutant (Fig.…”
Section: Responsiveness (Fig 4e; Supplementalmentioning
confidence: 62%
“…Characterization of the Gr mutant and overexpression of SlGR in tomato indicated that this gene influences a subset of ethylene responses in tomato (Barry et al, 2005;Barry and Giovannoni, 2006). However, overexpression of SlGRL1 in tomato causes inhibition of a subset of ethylene responses that overlap but are distinct from those observed in the Gr mutant and CaMV35S::SlGR lines (Fig.…”
Section: Discussion Variation In Ethylene Signaling Components and Evmentioning
confidence: 99%
See 3 more Smart Citations